Hepatitis B Immunisation amongst doctors and laboratory personnel in KwaZulu-Natal, South Africa - Feroza Y. Khan (African Journal of Primary Health Care & Family Medicine, 2013)
Background: Hepatitis B virus (HBV) infection is the most easily transmitted blood-bornepathogen and is an occupational hazard for health care workers (HCWs). Despite the factthat infection is preventable through vaccination and post-exposure immunoglobulin therapy, many HCWs are unaware of the risks of HBV infection and of appropriate preventative measures. This study is unique in the South African setting as it focuses on the exposure,attitude and knowledge of doctors to HBV infection.